IMPLEMENTASI KULINER TRADISIONAL MINAHASA SEBAGAI UNIQUE SELLING POINT DALAM PENINGKATAN DAYA SAING HOTEL: STUDI KASUS ROGERS HOTEL MANADO - Agustinus Walansendow; Bet El Silisna Lagarense; Jeskrispen Lagarense (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2025)
This study examines strategies for utilizing Minahasan traditional cuisine as a unique selling point (USP) to enhance the competitiveness of Rogers Hotel Manado. As a four-star hotel strategically located in the center of Manado City, Rogers Hotel faces intense competition from similar hotels offering standard facilities and services. Minahasan traditional cuisine, rich in flavor and cultural value, possesses significant potential as product differentiation that can create unique experiences for guests. This research employs a qualitative method with a case study approach through in-depth interviews with Rogers Hotel management, executive chef, food and beverage department staff, and hotel guests. Data was also collected through direct observation of kitchen and restaurant operations, as well as documentary studies of menus, marketing strategies, and guest satisfaction data. The findings reveal that Rogers Hotel has integrated Minahasan traditional cuisine through breakfast buffets featuring local specialties, signature dishes in the restaurant, and Minahasan-themed culinary events. This implementation has positively impacted the hotel with a 15% increase in occupancy rate during specific periods, improved guest satisfaction particularly among international tourists, and strengthened brand image as a hotel that promotes local wisdom. Success factors include management commitment, partnerships with local suppliers, chef competency in preparing traditional dishes to international standards, and promotional strategies through social media and collaboration with travel agents. Challenges encountered include taste standardization to maintain authenticity while meeting international guest preferences, continuity of quality ingredient supply, and educating guests about Minahasan culinary philosophy.